The Use of Attribute Charts Strategy to Improve Students’ Ability in Writing Descriptive Texts in Class VII SMP Negeri 1 Bangun Purba - Rosmanidar (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2022)
Writing is a way of expressing ideas, experiences, thoughts, and feelings and it becomes one of the skills that must be achieved by the seventh grade students. Producing a variety of short functional texts such as descriptive text raises the difficulty because of the different writing conventions including language components such as grammar, vocabulary, and spelling between Indonesian and English. The use of Attribute Charts strategy is the way to find out the effective strategy to help the students in writing the correct adjectives in order to improve the students‟ skills in descriptive writing. There are two purposes of this study. The first is to explain and describe the use of Attribute Charts as the strategy in teaching writing descriptive text to the grade VII of State Junior High School. The second is to find out how well the use of Attribute Charts as an alternative strategy in teaching writing descriptive text that gives a valuable contribution to the development of teaching writing. The subject of this research is 30 students of VII class of Junior SMP N 1 Bangun Purba in academic year 2022/2023. In order to achieve the purposes of the study, I designed an action research that was carried out through cycle 1 and cycle 2. I used observation, interview, and test as the instruments in collecting the data. The first meeting was used for conducting the pre-test. The second and third meetings were used to conduct cycle 1 and cycle 1 test, the fourth meeting was used to conduct cycle 2, and the last meeting was used to hold post-test. Based on the research, the students‟ progress during the teaching learning activity by using Attribute Charts is good. The writing aspects such aspects as organization, content, grammar, style in expressing ideas, and punctuation are improve in each cycle. It is realized by the significant result of the pre-test that is low (48.8), and the post-test which is high (70.1). Based on the result above, the Attribute Charts strategy can be one of effective strategies to improve the students‟ ability in writing descriptive text. This study suggests the teachers to use Attribute Charts as the strategy in teaching writing, especially in writing descriptive text.